Novel Missense and Splice Site Mutations in USH2A, CDH23, PCDH15, and ADGRV1 Are Associated With Usher Syndrome in Lebanon - Jaffal, Lama; Akhdar, Hanane; Joumaa, Hawraa; Ibrahim, Mariam; Chhouri, Zahraa; Assi, Alexandre; Helou, Charles; Lee, Hane; Seo, Go Hun; Joumaa, Wissam H.; El Shamieh, Said (Frontiers in Genetics, 2022)
Expand the mutation spectrum by searching the causative mutations in nine Lebanese families with USHER syndrome (USH) using whole-exome sequencing. The pathogenicity of candidate mutations was first evaluated according to their frequency, conservation, and in silico prediction tool. Then, it was confirmed via Sanger sequencing followed by segregation analysis. Finally, a meta-analysis was conducted to calculate the prevalence of USH genes in the Lebanese population. Three missense mutations, two splice site mutations, and one insertion/deletion were detected in eight of the families. Four of these variants were novel: c.5535C>A; p.(Asn1845Lys) in exon 41 of CDH23, c.7130G>A; p.(Arg2377Gln) in exon 32 of ADGRV1, c.11390-1G>A in USH2A and c.3999-6A>G in PCDH15. All the identified mutations were shown to be likely disease-causing through our bioinformatics analysis and co-segregated with the USH phenotype. The mutations were classified according to the ACMG standards. Finally, our meta-analysis showed that the mutations in ADGRV1, USH2A, and CLRN1 are the most prevalent and responsible for approximately 75% of USH cases in Lebanon. Of note, the frequency USH type 3 showed a relatively high incidence (23%) compared to the worldwide prevalence that is around 2-4%. In conclusion, our study has broadened the mutational spectrum of USH and showed a high heterogeneity of this disease in the Lebanese population.